Mulheres em luta: feminismos e Direito nas ocupações da Izidora - Thais Lopes Santana Isaias (2017)
This dissertation is based on feminist epistemologies and focuses on the urban occupations of Izidora, divided into the Rosa Leão, Esperança and Vitória communities, occupancies of idle land for about 30 thousand homeless people. This land is located in an urban expansion area of Belo Horizonte with a strong real estate speculation rate. Contrary to the patriarchal and racist social imaginary, built by recurring white male visibility in the struggles for occupying space, poor black women are the majority of the population and popular leaderships in Izidora. This is linked to the social dynamics of capitalist conception of space and production, reproduction and care, sustained by the intersectionality of gender, race and class, which unfolds into a violent system of spatial segregation, sexual and racial division of labor, and transfers almost exclusively to women, especially the poor and black ones, responsibilities related to the domestic sphere and maternity. Thus, lack of access to basic rights affects them particularly, and leads them into occupance as they struggle to survive. This scenario viscerally dialogues with the Law. Izidora´s conflict is crossed by disputes that pass in the justice system, whose institutional answers are given in the majority of the times to disregard the histories and spaces of the occupations, categorizing them as invasions, which results in orders of forced removal. It happens that the hegemonic positioning of the Law, made up by the discourse of applying universal and neutral rules, is done as a class political, patriarchal and racist political position elevated to the status of mandatory norm. However, through the spatialization and historicization of the struggle of occupations, it is perceived that dwellers question this position, claiming the recognition of rights and ways of life. Thus, encounters of multiple and simultaneous trajectories in the space of resistance provoke displacements not only in economic terms, in the sense of a redistribution of land, but also of gender and race, resulting in new, more empowered subjectivities. We also see the disorganization of gender roles through an everyday performance that deconstructs the boundaries between personal and political. Thus, they resignify the meanings of occupying, of woman, of public and private, of black identity. They also charge for the re-dimensioning of the law, marking the need to reverse traditional starting points to legal practice, whatever they might be, universalizing statements, to adopt the application of the current statements from the concrete contexts, paying attention to subalternized collectivities, entitled here as feminist spatial turn of Law.